2013
DOI: 10.1007/s00404-013-2796-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcome in triplet, quadruplet and quintuplet gestations following ART: a 11-year study

Abstract: Preterm labor and preterm prematurity were the commonest complications. Neonatal mortality and morbidity was significantly increased in quadru- and quintuplets. Prophylactic interventions were not used in an attempt to prevent preterm labor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
3
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 20 publications
4
22
3
3
Order By: Relevance
“…In these pregnancies, the average pregnancy age at delivery ranges from 31 to 33 completed weeks of gestation, with a majority of triplets being born before the 35th week [25]. It is evident that this prematurity is accompanied by high rates of neonatal complications which include both neonatal mortality and morbidity [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these pregnancies, the average pregnancy age at delivery ranges from 31 to 33 completed weeks of gestation, with a majority of triplets being born before the 35th week [25]. It is evident that this prematurity is accompanied by high rates of neonatal complications which include both neonatal mortality and morbidity [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that this prematurity is accompanied by high rates of neonatal complications which include both neonatal mortality and morbidity [6]. Although gestational hypertension and its complications, first and foremost preeclampsia, also contribute to the risk of preterm delivery in triplet pregnancies, the majority of cases is complicated by preterm labor and cervical shortening [5]. Notably, chorionicity has also been proven to be a risk factor for earlier delivery in triplets with dichorionic pregnancies having been reported to deliver more likely <30 weeks of gestation than trichorionic pregnancies [7].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, 54% of quadruplet and 100% of quintuplet pregnancies had at least one death, while the average weight at birth was 750 g for dead quadruplets and 1341 g for surviving quadruplets (p < 0.0007). Chibber in 2003 [102] in a study including 100 triplet, 27 quadruplets, and 10 quintuplet pregnancies showed that low birth weight is crucial for perinatal mortality and morbidity, with low birth weight complicating most of the 34 neonatal deaths in the quadruplet and quintuplet groups. Multiples are at increased risk of growth problems compared to singletons, with the degree of intrauterine growth restriction to increase as the number of fetuses increase.…”
Section: Complications and Management Of Quadruplet/quintuplet Pregnamentioning
confidence: 99%
“…A low Apgar score at birth is a common concern for neonatologists when a high-order pregnancy ends. Chibber in 2003 [102] highlighted the differences between triplet and higher pregnancies when the Apgar scores of the first and fifth minute were compared. The mean first-minute Apgar score for triplets was 7.8, while for quadruplets and quintuplets was only 6.2 (p < 0.01).…”
Section: Complications and Management Of Quadruplet/quintuplet Pregnamentioning
confidence: 99%
“…1–6 Triplets are admitted to a neonatal intensive care unit in 50–90% of cases, 4,79 compared with about 24% of twins and 3% of singletons. 10 Perinatal death occurs in 4.5–15% of triplets, 4,5,7,9,1115 compared with 2.0% of twins and 0.45% of singletons. 2 Most of the excess neonatal morbidity and mortality among triplets is directly attributable to extremely preterm birth.…”
Section: Introductionmentioning
confidence: 99%